Robot-assisted laparoscopy in benign gynecology: Advantageous device or controversial gimmick?. (November 2017) - Madueke-Laveaux, Obianuju Sandra; Advincula, Arnold P.
Abstract : The growth of robot-assisted laparoscopic surgery has been exponential since its FDA approval for use in gynecologic surgery in the spring of 2005; however, controversy surrounding its use has been associated with this rise in utilization. Much of this discussion has pitted the conventional laparoscopist against the robotic surgeon particularly as it relates to issues such as operative time, costs, and the current scientific evidence. Although drawbacks exist in robotic technology, there are also clear and obvious advantages that are difficult to quantify in the scientific literature but evident to users. This chapter highlights the current state of affairs regarding the scientific literature with an evidence-based focus on the most commonly applied application – benign hysterectomy.